2020
DOI: 10.1007/s11157-020-09523-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochar physicochemical properties: pyrolysis temperature and feedstock kind effects

Abstract: Biochar is a pyrogenous, organic material synthesized through pyrolysis of different biomass (plant or animal waste). The potential biochar applications include: (1) pollution remediation due to high CEC and specific surface area; (2) soil fertility improvement on the way of liming effect, enrichment in volatile matter and increase of pore volume, (3) carbon sequestration due to carbon and ash content, etc. Biochar properties are affected by several technological parameters, mainly pyrolysis temperature and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
703
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,592 publications
(751 citation statements)
references
References 188 publications
(239 reference statements)
33
703
1
14
Order By: Relevance
“…Additionally, it was confirmed that there were hydrophilic functional groups on the surface and pores of biochar with a high affinity for water; biochar application was shown to increase soil water retention more in a sandy soil than a loamy soil or a clay soil (Mandal et al 2020). Biochar also showed a positive impact on surface area of soil (Anawar et al 2015), which varied with biochar types (Tomczyk et al 2020). For example, biochar (10%)-amended soil had 3 times higher surface area than untreatedd soil (Tomczyk et al 2019).…”
Section: Physical Propertiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, it was confirmed that there were hydrophilic functional groups on the surface and pores of biochar with a high affinity for water; biochar application was shown to increase soil water retention more in a sandy soil than a loamy soil or a clay soil (Mandal et al 2020). Biochar also showed a positive impact on surface area of soil (Anawar et al 2015), which varied with biochar types (Tomczyk et al 2020). For example, biochar (10%)-amended soil had 3 times higher surface area than untreatedd soil (Tomczyk et al 2019).…”
Section: Physical Propertiesmentioning
confidence: 95%
“…However, in a field study, application of a paddy straw-derived biochar (biochar pH was 10.50) to a sandy soil (soil pH 5.24) increased the pH of the soil by 4.5 units compared to the control (El-Naggar et al 2018b). Moreover, a high dose (50 and 100 t ha −1 ) of biochar (pH 9.40) increased the pH of an Alfisol and, consequently, reduced exchangeable Al concentration in the soil (Tomczyk et al 2020). observed that application of biochar (10, 20, 40, and 60 t ha −1 ) had no impact on soil pH in a semi-arid region, which was consistent with the results reported by Werner et al (2018) who found that the pH of a sandy loam soil was not changed with addition of biochar.…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, biochar (BC) has attracted increasing interest as far as its utilization as filler for polymer-based composites, either thermoplastics or thermosets, is concerned [19,20]. BC is usually obtained from the pyrolysis of agricultural and forestry wastes [21], and its structure can be tuned depending on the pyrolysis conditions; in particular, by adjusting the temperature and the oxygen flow, the degree of internal porosity and the presence of different functional groups anchored to the surface can be tailored [22]. The interest towards BC lies in its intriguing properties, such as high chemical and thermal stability, great electric properties, and very large surface area [23], combined with its cost effectiveness and low environmental impact [24].…”
Section: Introductionmentioning
confidence: 99%
“…High residence time also affects the quality and amount of biofuel obtained (Tippayawong et al, 2008). In slow pyrolysis, the major by-product obtained is biochar (Tomczyk et al, 2020). The slow pyrolysis process takes more time (up to an hour) for completion as compared to flash and fast pyrolysis.…”
Section: Introductionmentioning
confidence: 99%